National Cultural Specificity of Speech Behavior in English and Uzbek - Tulyaganova Nargiza Farxod qizi; Yusupova Shoira Batirovna (Genius Journals, 2022)
We know that there are many different ways to learn foreign languages. One of the effective way is reading books in their original form . It helps us to speak like native speakers . Because it not only improves students' reading skills, but also helps to increase vocabulary. In addition , it gives more information about the culture and customs of the country which the language is being studied. In this article, we will talk about the positive influence of the culture and lifestyle in learning foregn languages . This article highlights some polite words and soft phases that exist in English and Uzbek, compare their similarities and differences in the two languages.
Keywords: Speech Behavior; Linguocultural; Interlocutor; Addressing